PEMBUATAN BRIKET DARI LIMBAH CANGKANG INTI SAWIT (PALM KERNEL SHELL) DAN SERABUT KELAPA - juni, st nabila risky; Pratama, Irham (UIR Press, 2026)
The utilization of biomass waste as an alternative energy source has gained increasing attention as a strategy to reduce dependence on fossil fuels. Palm kernel shells and coconut fiber are abundant plantation wastes in Indonesia; however, their utilization remains suboptimal. This study aims to analyze the characteristics of briquettes produced from palm kernel shells, coconut fiber, and their mixtures based on calorific value, moisture content, ash content, volatile matter, and fixed carbon. An experimental design with varying raw material compositions was employed, consisting of 100% palm kernel shells, 75:25, and 50:50 ratios (palm kernel shells:coconut fiber). The briquette production process included carbonization, grinding, mixing with starch adhesive, molding, and drying. The quality of the briquettes was evaluated through proximate analysis and calorific value measurement using a bomb calorimeter. The data were analyzed using descriptive methods and one-way ANOVA to determine the effect of composition variation on briquette characteristics. The results indicate that briquettes made from 100% palm kernel shells produced the highest calorific value of 6334.35 cal/g, while mixed briquettes ranged between 4900–5600 cal/g. The addition of coconut fiber increased moisture content and volatile matter, while reducing calorific value and fixed carbon. ANOVA results confirmed that variations in raw material composition significantly affected all tested parameters. From a practical perspective, palm kernel shells are recommended as the primary raw material for producing high-energy briquettes, while the incorporation of coconut fiber can enhance biomass waste utilization despite lowering calorific performance. This study contributes to the development of sustainable and environmentally friendly biomass-based alternative energy technologies